2004
DOI: 10.1111/j.1600-0684.2004.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

SIV‐induced activation of the blood‐brain barrier requires cell‐associated virus and is not restricted to endothelial cell activation

Abstract: It has never been determined if activation of the blood-brain barrier (BBB) during simian immunodeficiency virus/human immunodeficiency virus (SIV/HIV) infection is a function of high levels of circulating virus or if the virus has to be within a cell capable of crossing the BBB to activate it. In vitro models of the BBB are becoming recognized as an acceptable method for determining the cellular events associated with HIV neuroinvasion. Cell free virus (when added in the physiologically relevant lumen) althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…These studies showed that there was a requirement for SIV-infected cells to cross an in vitro BBB model to activate both the BMECs and astrocytes in a manner similar to that observed in vivo (MacLean et al , 2004a; MacLean et al , 2004b). Using immediately ex vivo microvessels obtained from encephalitic brains we demonstrated considerably lower levels of ZO-1 protein compared with microvessels obtained from control brains (MacLean et al , 2005).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…These studies showed that there was a requirement for SIV-infected cells to cross an in vitro BBB model to activate both the BMECs and astrocytes in a manner similar to that observed in vivo (MacLean et al , 2004a; MacLean et al , 2004b). Using immediately ex vivo microvessels obtained from encephalitic brains we demonstrated considerably lower levels of ZO-1 protein compared with microvessels obtained from control brains (MacLean et al , 2005).…”
Section: Introductionmentioning
confidence: 84%
“…We developed in vitro and ex vivo models of the BBB suitable for studies of SIV encephalitis (MacLean et al , 2005; MacLean et al , 2002; MacLean et al , 2004a; MacLean et al , 2004b). These studies showed that there was a requirement for SIV-infected cells to cross an in vitro BBB model to activate both the BMECs and astrocytes in a manner similar to that observed in vivo (MacLean et al , 2004a; MacLean et al , 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…While circulating monocytes are not thought to be productively-infected, the increased numbers of primed monocytes would likely lead to an increased potential for trafficking of cells capable of being infected to brain. The presence of infected monocytes is known to activate endothelial cells of the BBB to express CD106 (MacLean et al, 2004a, MacLean et al, 2004b and leads to disruption of tight junction proteins including ZO-1 and claudin 5 (Andras et al, 2003, Ivey et al, 2009b, Kanmogne et al, 2007, Luabeya et al, 2000, Persidsky et al, 2006, Huang et al, 2009. In contradistinction to CD106 expression, the loss of tight junction proteins is largely limited to areas close to viral infected cells (Luabeya et al, 2000, Andras et al, 2003, Kanmogne et al, 2005, Kanmogne et al, 2007, Persidsky et al, 2006, and Renner et al, in press.…”
Section: Terminal Diseasementioning
confidence: 99%
“…Expression of CD106 was not limited to areas immediately adjacent to viral-infected cells, but was diffuse throughout brain, remaining elevated through at least 23 weeks post infection (well beyond peak viral load and establishment of viral set point). We have shown that CD106 expression is upregulated on endothelial cells and astrocytes following incubation with either viral-infected cells or their supernatants (MacLean et al, 2004a, MacLean et al, 2004b, and by others on astrocytes using Theiler's Murine Encephalomyelitis Virus (Rubio et al, 2010). That cell-free virus was able to stimulate endothelial cells to express CD106 may explain the diffuse staining earlier observed by Sasseville et al Both HIV and SIV use two cellular receptors in combination for infection: the CD4 molecule and a chemokine receptor, the two most common being CCR5 and CXCR4 (Moore et al, 2004).…”
Section: Acute Infectionmentioning
confidence: 99%
See 1 more Smart Citation